2007
DOI: 10.1007/s12035-007-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and Multiple Sclerosis

Abstract: This review discusses clinical and preclinical evidence that supports the use of cannabinoid receptor agonists for the management of multiple sclerosis. In addition, it considers preclinical findings that suggest that as well as ameliorating signs and symptoms of multiple sclerosis, cannabinoid CB(1) and/or CB(2) receptor activation may suppress some of the pathological changes that give rise to these signs and symptoms. Evidence that the endocannabinoid system plays a protective role in multiple sclerosis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 100 publications
1
67
0
1
Order By: Relevance
“…Clinical studies reported only limited side effects, the most frequent being the dizziness/light-headedness; it is important to highlight the low lethality of cannabis overdose, consistent with experimental data showing the absence of CB1 receptor binding in the respiratory centers of the brainstem (Robson, 2001;Pertwee, 2007).…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Clinical studies reported only limited side effects, the most frequent being the dizziness/light-headedness; it is important to highlight the low lethality of cannabis overdose, consistent with experimental data showing the absence of CB1 receptor binding in the respiratory centers of the brainstem (Robson, 2001;Pertwee, 2007).…”
Section: Introductionsupporting
confidence: 71%
“…Evidences of the clinical efficacy of cannabinoids in MS patients derive from studies showing that the administration of cannabinoid agonists may improve the spasticity, the pain, and the quality of sleep (see for review, Pertwee, 2007). However, a recent meta-analysis of clinical trials reported that cannabinoid agonists treatment does not induce significant effects when objective assessments are compared, even if a subjective improvement of symptoms are reported by patients (Lakhan and Rowland, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials present positive effects of either cannabis, Δ 9 -THC or other CB agonist on spasticity, spasms and pain among other signs of MS (Croxford, 2003; Pertwee, 2007; Rog, 2010; Notcutt et al, 2012). Use of Sativex® (Nabiximol) an oromucosal spray of cannabis extract containing fixed concentrations of Δ 9 -THC and cannabidiol (CBD), results in symptomatic improvement in patients with MS.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…In contrast, when an inverse agonist of the CB 1 receptor (SR141716A) was applied, the EAE was worsened likely by releasing pro-inflammatory cytokines in the mouse brain and spinal cord (Saito et al, 2012). Underlying the role of CB 1 receptors during neuromodulation and inflammation, work on CB 1 receptor −/− mice suggest that these animals are more susceptible to neurotoxicity and damage when compared to wild-type mice (Jackson et al, 2005; Pertwee, 2007). Taken together these results suggest that in MS, the neuroprotective roles of CB 1 and CB 2 receptors might be impaired and their enhancement could provide new therapeutic approaches.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…However, studies with a sublingual cannabis spray (Sativex®) have likewise had minimal impact on objective outcomes such as the Ashworth Scale [31,36,47], but have shown consistent subjective, patient-assessed improvements in spasms and spasticity. As cannabis affects cognitive processes [22], it can be argued that whilst patients feel subjectively improved due to mood modulation these may not be objectively demonstrable at cannabinoid doses that do not induce significant cannabimimetic, psychoactive effects [25,30,32,36,40,42]. However, positive effects with few exceptions [30] have been reported following treatment with THC or medical cannabis extracts [32,36,38,40,42,46,47].…”
Section: Cannabinoids In Spasticitymentioning
confidence: 99%